Sinergi Perguruan Tinggi dengan Tentara Nasional Indonesia: Program Community Development Training - Freddy Johanis Rumambi (Jurnal Syntax Admiration, 2024)
The implementation of the Tri Dharma of Higher Education activities, namely education, research and community service (PkM), needs to be carried out through synergy with stakeholders, including the World of Education and the Indonesian National Army in order to have a sustainable impact. Universities (academics) especially in PkM activities involving the role of the Indonesian National Army. The existence of universities in the life of the nation and state plays an important role through the implementation of the Tri Dharma of Higher Education, namely education, research and community service. Community service is a forum for lecturers and students to actualize their field of knowledge. The synergy between the TNI and the world of education will not only bring benefits to both parties but also to society and the country as a whole. This collaboration is an investment in forming a young generation who is educated, disciplined and has a sense of love for the country. The synergy between the TNI and the world of education is a form of multi-dimensional collaboration that can bring many benefits. Partnerships ranging from curriculum improvements, skills training, to joint research between these two entities can contribute to strengthening the country's human resources and capabilities. This is not only an investment for the future, but also a concrete effort to realize the nation's security, progress and prosperity.